KOMUNIKASI KESEHATAN DALAM MENINGKATKAN POLA HIDUP SEHAT KARYAWAN MELALUI PROGRAM PARADIGMA SEHAT 4P DI PT. TELEKOMUNIKASI INDONESIA TBK, PEKANBARU - Nomalia, Tessa; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Lack of employee health concern affects performance in getting optimal results. To support it, PT. Telecommunication Indonesia Tbk, Pekanbaru provides facilities in the form of Healthy Paradigm 4P program to improve healthy lifestyle of employees is a program of Health Foundation Telkom Center of Healthy Diet, Healthy Activity Pattern, Healthy Mindset and Healthy Spiritual Pattern. This study aims to determine the form of health communication, health communication barriers and health communication media at PT. Telecommunication Indonesia Tbk, Pekanbaru This research uses qualitative method with descriptive approach. Research subjects amounted to 7 people. With research object health communication unit Human Resource Development (HRD) in improving healthy lifestyle of employees through 4P health paradigm program at PT. Telecommunication Indonesia Tbk, Pekanbaru. Data collection techniques use observation, interview and documentation. While the data analysis techniques using qualitative data analysis with the presentation of descriptive analysis according to Huberman and Miles. And examination techniques validity of data by extension of participation and triangulation. The results of the research show that the 4P Health Paradigm program is conducting Health Communication from the Human Resource Development (HRD) unit in improving the healthy lifestyle of employees through the 4P Health Paradigm program at PT. Telecommunication Indonesia Tbk, Pekanbaru seen through the form of communication is the form of interpersonal communication, group communication and organizational communication. Human Resource Development (HRD) units use media such as websites, emails, phones, banners, and brochures. The 4P's Healthy Paradigm Program Process has barriers that come from sources and employees.